A Perplexing Case of Pituitary Apoplexy Masquerading as Meningoencephalitis - Rahman, Aminur; Mondal, Sharna Purna; Ahmed, Muhammed Jamil; Md Russel, Abul Hasnat; Agarwala, Ajay Kumar; Twinkle, Furial Quraishi; Dastegir Khan, Shahjada Mohammad; Paul, Biplob; Ali, Zahed (Bangladesh Journal of Medicine, 2021)
Pituitary apoplexy (PA) is extremely rare in children and adolescents. It is a life-threatening condition usually results from sudden hemorrhage or infarction induced swelling in a pituitary adenoma. The clinical manifestations of PA include severe headaches, impaired consciousness, fever, visual disturbance, and variable ocular paresis. Therefore, the presence of meningeal irritation may lead to misdiagnosis as a case of meningoencephalitis or spontaneous subarachnoid hemorrhage, and delay in the proper management of the disease. We report a case of 17-year-old pubertal boy who developed sudden severe headache, vomiting, slurring of speech and abnormal behaviour followed by impaired sensorium with fever. The patient who was initially diagnosed with meningoencephalitis (ME) based on clinical presentation and cerebrospinal fluid (CSF) analysis, which was consistent with bacterial meningitis. MRI of brain was performed, confirming a pituitary macroadenoma with hemorrhage and ischemic changes in both basal ganglia and pons. A complete analysis of the pituitary hormones revealed decreased cortisol and thyroid hormone level and hyperprolactinemia and he was subsequently started on placement corticosteroid and L-thyroxine therapy and cabergoline. After 14/ days of antimicrobial therapy with ceftriaxone and ampicillin, the patient improved and was discharged on hormone replacement therapy and surgical advised. Hereby, we report our case with a review of literatures. Bangladesh J Medicine July 2022; 33(1) : 85-88